PENINGKATAN HASIL BELAJAR PESERTA DIDIK SEKOLAH DASAR PADA PEMBELAJARAN PKn DENGAN MENGGUNAKAN TEKNIK MIND MAP - Feriani Putri Sari; Reinita (Universitas Katolik Musi Charitas, 2019)
The purpose of this study was to describe the learning outcome of students in learning Civic Education by using Mind Map technique in class V SDN 04 Situjuah Banda Dalam. This type of research is a classroom action research using qualitative and quantitative approaches. The subjects were teacher and students of class V. The research was conducted in two cycles. The procedure includes research, planning, implementation, observation, and reflection. The results showed increased in 1) RPP of first cycle 83.93% and second cycle 92.86% , 2) Implementation in the teachers aspect of first cycle 81.25% and second cycle 93,75% , 3) Implementation in the student aspect of first cycle 78,125% and second cycle to 93.75% , 4) Student learning outcomes of first cycle 73.10 and second cycle 82.78. It can be concluded, using of Mind Map technique can improve student learning outcomes in Civics learning.